Kant's reform of metaphysics : the critique of pure reason reconsidered - de Boer, Karin (New York: Cambridge university press, 2020)
Kant's Reform of Metaphysics is the first book-length study to interpret Kant's Critique in view of his efforts to turn Christian Wolff's highly influential metaphysics into a science.
1. Wolff, Crusius, and Kant; 2. The (3z(BThorny Paths of Critique(3y(B; 3. Ontology, Metaphysics, and Transcendental Philosophy; 4. Things in Themselves, Transcendental Objects, and Monads; 5. The 1781 Transcendental Deduction of the Pure Concepts of the Understanding; 6. The Schematism of the Pure Understanding; 7. Transcendental Reflection; 8. Kant's Projected System of Pure Reason; Conclusion.s
Includes bibliographical references and index.
Keywords: Kant, Immanuel, 1724-1804.